OPTIMIZATION OF THE EARLY WARNING SYSTEM IN FLOOD DISASTERS - Muttaqin, Helmy Faisal; Fauzi, Esa (CENTRAL ASIA AND THE CAUCASUS, 2022)
Flood is a natural disaster that threatens all residents who are always active in the river, especially in the area around the river. Flash floods are natural disasters caused by overflowing river water that leaks due to river water runoff that exceeds the capacity of the river and enters low-lying areas of the earth's surface such as river valleys, basins and usually carries material or garbage in the river. . In the era of globalization, the development of this technology is increasingly rapid, where there is an early warning system. An early warning system is a series of systems that notify you when things have a negative impact and can minimize those impacts. It would be dangerous to reach the existence of this resident. So that the occurrence of flash floods can endanger the watershed. So with a technology called the Internet of Things that can be built into the system, it can provide an early warning system that provides warnings in the form of sirens and LED lights and sends early warning information so that more serious disasters can be avoided.